We have to change; they stay the same: a qualitative study of Chinese international students’ academic experiences at an Australian university - qu, mingxin; Song, xianlin (Journal of International Students, 2024)
Overseas student integration and difficulties in adjusting into the academic life of the host country are often posited as personal failures, and international education scholarship focuses heavily on the notion of failure. However, the categorization of international students is premised on them not being active subjects in the curriculum and the ways in which they can contribute to internationalization of higher education. The current study addresses this negative characterization through qualitative methodology, observing and interviewing 24 Chinese international students at an Australian university. Conducted during the COVID pandemic period, this study offers new insights into how the shift to online learning exacerbated the failure of the teaching, learning, and curriculum models that predominate in Australian universities. We call for a rethinking of international students’ education; as the pandemic subsides, deeper conversations are necessary over the continued prevalence of the deficit model while considering international students’ agency in their learning practices.